(untitled) (Journal of Rangpur Medical College, 2026)
Background: Diabetes mellitus increases susceptibility to viral skin infections through impaired immunity, yet evidence from low-income settings is scarce. Objective: This study examined demographic, socioeconomic, and glycemic correlates of viral skin infections among diabetic patients in Bangladesh. Methods: This cross-sectional study was conducted among 173 diabetic patients with clinically confirmed viral skin infections at the Department of Dermatology, BIRDEM General Hospital, Dhaka, Bangladesh from June 2024 to July 2025. Demographic variables, socioeconomic status (SES), environmental exposures, and glycemic control were analyzed. Results: Young adults constituted the largest group (45.7%), and males predominated (64.2%). Uncontrolled glycemia was observed in 46.2% of cases. Lower SES was strongly associated with herpes zoster (61.3%) and genital herpes (61.0%). Multivariable analysis identified low SES (aOR 2.60, 95% CI 1.40–4.85), uncontrolled diabetes (aOR 2.25, 95% CI 1.20–4.25), slum residence (aOR 2.35), and jail confinement (aOR 2.50) as independent predictors. Conclusion: Viral skin infections in diabetic patients are shaped by socioeconomic vulnerability and poor glycemic control. J Rang Med Col. 2026 Mar;11(1): 27-32